Geburten/Kontrolle Reproduktionspolitik im 20. Jahrhundert - Mesner, Maria (2010)
The volume aims at a comprehensive historical reconstruction of policies, conflicts, attitudes, and regulations covering the diverse field of human reproduction. The analysis is based on two case studies: the United States of America and Austria. While both countries are part of the geographic and conceptual region called the "north-Atlantic world", they occupy significantly different positions within the global power structure, the respective relations between state, religion and society, the nature of their political cultures, etc. While it is impossible to re-construct a universal history of population policies on the basis of the two case studies, in the concluding chapter more universal premises relating to 20th century trends and developments beyond the case studies are suggested. To enable a comprehensive, yet focused comparison the analysis concentrates on three aspects of reproductive policies: sexual advice centers in the cities of New York and Vienna during the interwar period; 20th century policies aimed at the interface between workplace and child care; and the abortion conflicts taking place in the last third of the 20th century. These fields are conceptualized as "arenas"-i. e., spaces or complex social situations where groups and individuals interested in a given issue meet and interact, attempt to establish their world views, and then transform them into commonly accepted norms and regulations. Events, actors, and developments are thoroughly re-constructed for each arena. Finally the arenas are analyzed in relation to social and political developments in which they are situated. Questions about trends and developments relevant for both case studies are addressed in a framework which is organized around notions of reproduction of the nation, of rationalization, and of globalization. The findings from the case studies are related to secular phenomena like migration, globalizing selective population policies, the emergence of international and transnational political bodies (private foundations, UN-organizations, NGOs). The comparison between the U.S. and Austria offers insights into the tensions inherent in modern reproduction between individual empowerment and political disciplining. The striking similarities and significant differences in the trajectories of reproductive policies in both case studies allow conclusions concerning an indissoluble dilemma of reproductive policies committed to "human progress." In the end, the volume contributes to a deeper understanding of the ambivalence inherent to modern reproduction.